Runx1 Deficiency in CD4+ T Cells Causes Fatal Autoimmune Inflammatory Lung Disease Due to Spontaneous Hyperactivation of Cells - Wong, W.F.; Kohu, K.; Nakamura, A.; Ebina, M.; Kikuchi, T.; Tazawa, R.; Tanaka, K.; Kon, S.; Funaki, T.; Sugahara-Tobinai, A.; Looi, C.Y.; Endo, S.; et al. (American Association of Immunologists, 2012)
The Runx1 transcription factor is abundantly expressed in naive T cells but rapidly downregulated in activated T cells, suggesting that it plays an important role in a naive stage. In the current study, Runx1−/−Bcl2tg mice harboring Runx1-deleted CD4+ T cells developed a fatal autoimmune lung disease. CD4+ T cells from these mice were spontaneously activated, preferentially homed to the lung, and expressed various cytokines, including IL-17 and IL-21. Among these, the deregulation of IL-21 transcription was likely to be associated with Runx binding sites located in an IL-21 intron. IL-17 produced in Runx1-deleted cells mobilized innate immune responses, such as those promoted by neutrophils and monocytes, whereas IL-21 triggered humoral responses, such as plasma cells. Thus, at an initial stage, peribronchovascular regions in the lung were infiltrated by CD4+ lymphocytes, whereas at a terminal stage, interstitial regions were massively occupied by immune cells, and alveolar spaces were filled with granular exudates that resembled pulmonary alveolar proteinosis in humans. Mice suffered from respiratory failure, as well as systemic inflammatory responses. Our data indicate that Runx1 plays an essential role in repressing the transcription of cytokine genes in naive CD4+ T cells and, thereby, maintains cell quiescence.